2012
DOI: 10.1007/s10336-012-0855-x
|View full text |Cite
|
Sign up to set email alerts
|

The number and coloration of white flank spots predict the strength of a cutaneous immune response in female Diamond Firetails, Stagonopleura guttata

Abstract: Colour variation in birds is often used to signal functional differences between individuals and sexes, though white plumage has usually been disregarded because white feathers were thought to be cheap to produce and hence unreliable signals. Here, we provide evidence for sex-specific morphological and colour differences in the strikingly patterned but apparently monomorphic Diamond Firetail (Stagonopleura guttata). We found that males had longer and darker tails, wider lores and a darker bill, while females h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 89 publications
3
35
1
Order By: Relevance
“…Indeed, our results are similar to a recent study that found carotenoid-based ornamentation was related to immunity in female American goldfinches (Spinus tristis) but not in males (Kelly et al, 2012). While it is becoming increasingly clear that discrete white plumage patches can be related to individual condition (McGlothlin et al, 2007), quality (Hanssen et al, 2006(Hanssen et al, , 2009Zanollo et al, 2012) or offspring quality (Remeš and Matysioková, 2013), very few studies have examined the reflectance of large white plumage areas (but see Bonato et al, 2009Bonato et al, , 2013. Bonato et al (2013) found a positive relationship between the white brightness of the genetic father and humoral immunity in offspring, a result quite similar to the one we found for innate immunity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, our results are similar to a recent study that found carotenoid-based ornamentation was related to immunity in female American goldfinches (Spinus tristis) but not in males (Kelly et al, 2012). While it is becoming increasingly clear that discrete white plumage patches can be related to individual condition (McGlothlin et al, 2007), quality (Hanssen et al, 2006(Hanssen et al, , 2009Zanollo et al, 2012) or offspring quality (Remeš and Matysioková, 2013), very few studies have examined the reflectance of large white plumage areas (but see Bonato et al, 2009Bonato et al, , 2013. Bonato et al (2013) found a positive relationship between the white brightness of the genetic father and humoral immunity in offspring, a result quite similar to the one we found for innate immunity.…”
Section: Discussionsupporting
confidence: 90%
“…White brightness may be associated with either the quantity or activity of complement enzymes or lysozyme that are primarily responsible for this aspect of the innate immune response (Matson et al, 2006). The results for females were similar to other recent studies that indicated the size, number or reflectance of white plumage patches is related to the strength of the immune response or parasite load in female birds (Hanssen et al, 2006;Zanollo et al, 2012;Blanco and Fargallo, 2013). Our results suggest that greater attention should be paid to the reflectance of large, white patches of plumage, which are infrequently examined in most avian studies despite being relatively common.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…From our (Zanollo et al. ) and Higgins () observations, birds appear to pair anew for each clutch of eggs. Birds are dimorphic in the number of white flank spots: females have more white spots than males (Zanollo et al.…”
Section: Methodsmentioning
confidence: 83%
“…; Zanollo et al. ). Male Diamond Firetails have an elaborate courtship display that combines four different traits: (1).…”
Section: Introductionmentioning
confidence: 97%